PENGEMBANGAN ALAT PERAGA KOTAK ENERGI MODEL INKUIRI TERBIMBING (APKEMIT) SEBAGAI PENUNJANG PEMBELAJARAN FISIKA SMA PADA MATERI SUHU DAN KALOR - Budiono Basuki; Aris Doyan; Ahmad Harjono (Postgraduate, University of Mataram, 2015)
The purpose of this research is to develop APKEMIT as learning tool for high school physics on temperature and heat concepts. This study used Borg & Gall approach on R & D which includes the step of development, pilot testing, and final testing. In the development stage, five APKEMIT models are produced: PKTSB, PW, PPSTUB, PK, and AB. Pilot testing stage is divided into two phase, limited testing and large scale testing. The first limited testing carried out on 6 eleventh grade science students in SMA 3 Mataram. The second phase carried on 2 groups (12 students) of accelerated tenth graders in SMA Negeri 1 Woha. Large-scale trials given to 8 groups (46 students) of tenth graders in SMA Negeri 3 Mataram. Pilot testing shows that APKEMIT is very good and ready to be used in learning activity. APKEMIT final testing stage is the stage to determine the effect of APKEMIT on the improvement of learning outcomes, which is determined by the Gain Score. Analysis shows that the gain of each model is: PKTSB Score of 0.50 (medium), PW of 0.15 (low), PPSTUB of 0.40 (medium), PK at 12:27 (low), AB of 0.34 (medium) and overall Gain Score at 0:36 (medium). This development received good response from the students with score 80.8% and according to observers, learning process has been going very well. The result of research and validation of test show that the developed APKEMIT become as references in subject temperature and heats concepts.